The outside edge : how outsiders can succeed in a world made by insiders - Kelsey, Robert, 1964- (Capstone, 2015)
"The brand new book from the international bestsellingself-help author Robert Kelsey's internationally bestselling self-help bookshave helped tens of thousands of people overcome fear of failureand under confidence. Now Robert is back and is here to debunk theever pervasive myths around the trail-blazing rebeloutsider ... As Robert says himself, the fashionable commentators are extremely keen to cry 'Be a rebel outsider and the modernworld will fall at your feet: your talent celebrated, your ideasworshiped'. If only it were true. In reality outsiders are usually disabled by feelings of alienation and disaffection, and bytheir inability to fit-in within a world made by insiders. Far from being celebrated, the vast majority of outsiders are potentially chained to a life of low-attainment, mental-isolation, frustration, bitterness and surrender. If you feel this way, all is not lost. The Outside Edge isall about learning to harness the unique vantage point you possessin order to give yourself the edge required to succeed. It will show you when to embrace your outsider status and go against convention, and when to play the game, do as the insiders do andmake sure you can get progress. Think of The Outside Edge as the life manual that will help you not only overcome negative feelings of exclusion but turn those into your USP - your edge. By getting The Outside Edge you can:[bullet] Gain insight into both the root causes of alienation and the all-encompassing negative consequences [bullet] Gain the confidence, guile and know-how to profitably "rebel". [bullet] Avoid pitfalls such as poor judgement, negativity andextremism [bullet] Unlock the key to success and address the real obstacles hindering your professional and personal growth"--